ANALISIS NILAI-NILAI PENDIDIKAN AKHLAK TENTANG SABAR DAN IKHLAS DALAM NOVEL SANG ABDI NDALEM KARYA ELIN KHANIN - Nabiilah Tsabitul Azmi; Nurul Mubin; Sofan Rizqi (JURNAL ILMIAH NUSANTARA, 2025)
This article discusses the values ​​of moral education about patience and sincerity in the novel Sang Abdi Ndalem by Elin Khanin and its relevance to contemporary Islamic education. This research was conducted using a descriptive qualitative approach through literature study, documentation, online data search, and interviews, with content analysis and discourse analysis techniques. The results of the study indicate that this novel contains profound moral lessons about the importance of patience and sincerity, which are reflected in the steadfastness in facing trials, obedience to orders, the ability to control oneself, and acceptance of destiny and sincerity in selfless charity. In addition to being a literary work, Sang Abdi Ndalem also has great potential as a source of learning moral education in the context of modern Islam. The inspiring narrative, rich cultural background, and moral values ​​conveyed subtly make this novel effective in enriching character learning methods. Thus, the use of this literary work in the world of education can be an interesting and meaningful alternative in forming a strong, patient, sincere, and noble Muslim personality in the contemporary era.